Designs for 24-vertex snarks - Forbes, Anthony D. (Utilitas Mathematica, 2018)
The design spectrum problem is solved for the thirty-eight 24- vertex non-trivial snarks. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.